Using Social Network Analysis in the Classroom: An Experiential Activity and Tool to Enhance a Sense of Community. (September 2019) - Dunn, Mary B.
This article presents an experiential exercise where students learn the basics of social network analysis, relate social networks to social capital, and analyze their own networks in the classroom. Instructors of all types of courses at both the undergraduate and graduate levels can use this activity to teach students about social networks and build a greater sense of community in the classroom. This article provides instructions for collecting students' social network data, teaching students about social networks as the basis for social capital, guiding students through basic social network analyses, and facilitating a discussion about ways to increase social capital for individuals and collectives. While engaging in this activity, students have opportunities to interact with other students and build high-quality relationships. In doing so, this exercise can facilitate a greater sense of community in the classroom, enrich the social capital for the collective, and promote students' learning.